Competitive Coefficients - Friedman, Lawrence (Management Science, 1959)
The value relationships among the competitors in a competitive situation are described by means of competitive coefficients. The competitive coefficient defines the indirect gain or loss to a competitor as a result of losses or gains by the other competitors. An example is given to illustrate the use of the coefficients in a game situation.